Recommendations on the certification of reference standards for structure identification of recombinant therapeutic proteins - O. B. Ustinnikova; R. A. Volkova; A. A. Movsesyants; V. A. Merkulov; V. P. Bondarev (Биопрепараты: Профилактика, диагностика, лечение)
Reference standards for structure identification of recombinant therapeutic proteins are essential for quality assessment of recombinant protein-based biotechnological medicinal products. The development and certification of such reference standards hold special relevance because of, firstly, the absence of international, national or compendial reference standards for a number of new or recently approved proteins and, secondly, the disruption of supply chains providing the biopharmaceutical industry of the Russian Federation with international reference standards. Moreover, international and national regulatory documents contain only general requirements for the procedure of reference standards certification but not the considerations specific to the standards for biotechnologicals’ structure identification, which vary with the production technologies for each individual active moiety. The aim of this work was to provide recommendations on the procedure for the development and certification of reference standards used to identify the structure of recombinant therapeutic proteins. These recommendations define 4 main stages of the procedure: stage 1 covers the development of requirements for the reference standard, including the justification of material and formulation choices, the elaboration of quality specifications, and the assessment of quality; stage 2 comprises the selection of analytical procedures and the establishment of the values for the certified parameters; stage 3 includes stability studies and shelf-life setting; and stage 4 involves the development of documentation for the reference standard. The paper dwells upon the scope of the stages, taking into account the specific considerations for recombinant therapeutic proteins and the use of reference standards. The recommendations are based upon the extensive experience in biotechnologicals testing and standardisation of the employees of the Scientific Centre for Expert Evaluation of Medicinal Products. These recommendations can provide a base for the establishment of protein-specific certification programmes for reference standards used in structure identification. This approach will allow for systematisation of the process for standards development and ensure the traceability of information and the validity of results. The reference standards certified in accordance with these recommendations can be considered primary standards, if necessary.